Kolaborasi Antar Aktor dalam Penanggulangan Stunting melalui Program DASHAT di Kabupaten Gowa - Sudirman, Rahmawati; Wahyuni, Sri (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Stunting remains a major public health problem in Indonesia, including in Gowa Regency, requiring cross-sector collaboration. One strategic initiative is the DASHAT (Healthy Kitchen to Overcome Stunting) program, which emphasizes community empowerment and multi-stakeholder involvement. This study analyzes collaboration among actors in stunting prevention through the DASHAT program using the collaborative governance framework of Emerson, Nabatchi, and Balogh (2012). The research applies a literature review method by examining policy documents, scientific articles, and official reports related to stunting policy, collaborative governance, and the DASHAT program. Data were analyzed using qualitative content analysis to identify actor roles, coordination patterns, and governance dynamics. The findings show that collaboration involves local government, health institutions, community organizations, and the private sector through shared planning, communication, and coordinated service delivery. Program effectiveness is influenced by institutional commitment, resource sharing, and community participation, although coordination at the local level remains a challenge. These results indicate that the success of the DASHAT program depends on the quality of collaborative governance among stakeholders.